2017
DOI: 10.1038/srep42027
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of mangiferin on myocardial ischemia-reperfusion injury in streptozotocin-induced diabetic rats: role of AGE-RAGE/MAPK pathways

Abstract: Hyperglycemia induced advanced glycation end products-receptor for advanced glycation end products (AGE-RAGE) activation is thought to involve in the development of cardiovascular disease in diabetics. Activation of AGE-RAGE axis results in the oxidative stress and inflammation. Mangiferin is found in the bark of mango tree and is known to treat diseases owing to its various biological activities. Thus, this study was designed to evaluate the effect of mangiferin in ischemia-reperfusion (IR) induced myocardial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 52 publications
(50 reference statements)
5
50
0
Order By: Relevance
“…It has been demonstrated in the myocardium that the activation of PI3K/AKT and MAPK/ERK pathways by procedures such as ischaemic pre-or postconditioning or by the administration of pharmacological agents is crucial for the salvage of the ischaemic/reperfused myocardium [37][38][39]. Herein, we demonstrated that silence of miR-23a and/or miR-92a activated PI3K/AKT and MAPK/ERK signaling pathways, since the phosphorylated levels of PI3K, AKT, MAPK, and ERK proteins were remarkably up-regulated by miR-23a and/or miR-92a overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated in the myocardium that the activation of PI3K/AKT and MAPK/ERK pathways by procedures such as ischaemic pre-or postconditioning or by the administration of pharmacological agents is crucial for the salvage of the ischaemic/reperfused myocardium [37][38][39]. Herein, we demonstrated that silence of miR-23a and/or miR-92a activated PI3K/AKT and MAPK/ERK signaling pathways, since the phosphorylated levels of PI3K, AKT, MAPK, and ERK proteins were remarkably up-regulated by miR-23a and/or miR-92a overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…Hou et al (2016) described mangiferin reduced AGE formation and decreased the mRNA and protein expression of receptor for AGEs in diabetic cardiomyopathy model rats. In addition, Suchal et al (2017) reported 2 attenuated ischemia-reperfusion induced myocardial injury in streptozotocin-induced diabetic rats by modulation of AGE-receptor/MAPK pathways which further prevented oxidative stress, inflammation and apoptosis in the myocardium. From the view point of structure-activity relationship, we will attempt to examine whether 1 and 2 have a similar inhibitory mechanism of AGEs formation because 1 and 2 belong to C-glucosyl-polyphenols.…”
Section: Samplesmentioning
confidence: 99%
“…The expression of Nrf2, HO-1, SOD, Akt and GSK-β and the mechanistic target of rapamycin (mTOR) and cyclin D were also increased by exposure to mangiferin. In an STZ-induced diabetic Wistar rat model, mangiferin improved antioxidant status and reduced apoptosis and inflammation [82]. This could be due to modulation of the AGE-RAGE/MAPK signalling pathways.…”
Section: Antioxidant Effectsmentioning
confidence: 92%